Avaliação da satisfação dos cardápios e do serviço prestado aos usuários de uma UAN universitária da cidade de Belém-Pa - CALANDRINI FILHO, Edson Jair Martins (2023)
Introduction: The Food and Nutrition Units (UAN) are spaces where healthy and safe meals are provided from the hygienicsanitary point of view. Objective: To evaluate the satisfaction of the menus and services provided in a UAN University of BelémPA. Methodology: This is a crosssectional, descriptive, exploratory and quantitative study carried out in a university restaurant in the city of Belém-PA, which serves an average of 7 thousand meals a day. The research was carried out from April to May 2019. Through the application of an electronic form, composed of 31 questions. The online tools were used: googleforms and QRcode in order to facilitate the voluntary participation of the users in the research. The evaluated items were: (1) Menu: appearance, aroma color, flavor texture / consistency, temperature, variety and value of meals. (2) Service: presentation of the team, attendance, form of distribution, hygiene of the environment, distribution and utensils, meal distribution schedule, infrastructure, service organization, sanitary facilities, queue waiting time and suggestions. Descriptive analysis was used to evaluate the database. Results: 310 clients participated in the study, 54.8% female and 45.2% male, 43.5% between 21 and 25 years old, with a predominance of 92.9% being undergraduate students. Regarding the menu item, 55.81%, 55.48% and 53.23% of users rated the menus as having a good appearance, color and temperature, respectively. Regarding the evaluation of the service, the users classified as good: 54.52 and 50.97% for the items hygiene of the environment and infrastructure of the restaurant, respectively. Regarding the value of the meal, 81.61% of the customers rated it as great. Conclusion: The satisfaction survey helped the UAN management team in the effective diagnosis of the offered menus, in the provision of the service and also in the actions of continuous improvement of the service, since most of the users answers were classified with a "good" index.